TEACHING ENGLISH MEDICAL TERMINOLOGY FOR MEDICAL STUDENTS VIA AUTHENTIC MOVIES - Israilova, Ilona (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
In the world theory and practice of teaching English, a careful selection of the content of teaching the language of specialty, which should satisfy the communicative needs of medical students in the field of their daily and professional activities, becomes especially in demand. In the context of the necessity to update the methods and technologies of modern education, professionally-oriented teaching of English in a medical university through the use of authentic film material is of particular relevance. This article is devoted to teaching English medical terminology through authentic fictional movies.